2011
DOI: 10.5172/conu.2011.157
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of a Russian version of the Social Support Questionnaire (SSQ6) in eastern European immigrants

Abstract: The Russian version of the SSQ6 has an internally consistent measure Cronbach's α 0.885 for the total scale. For the subscale SSQ6N (number of supporters) Cronbach's α was 0.907; for the subscale SSQ6S (satisfaction of support) Cronbach's α was 0.921. Two factors were extracted using factor analysis - Number of supporters and Satisfaction with social support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In contrast to our results, previous studies assessing the psychometric properties of the SSQ-6 reported a two-factor model with all SSQS items loaded to one factor, and all SSQN items to another. 20 , 21 An adaptation in a cohort of Russian-speaking immigrants in Portugal (N = 555) did not account for mean satisfaction and availability responses, but did find a two-factor structure to be the best fit and tested high for reliability. 20 In the population of Russian-speaking immigrants, the two factors extracted using a factor analysis were number of supporters and satisfaction with social support received.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In contrast to our results, previous studies assessing the psychometric properties of the SSQ-6 reported a two-factor model with all SSQS items loaded to one factor, and all SSQN items to another. 20 , 21 An adaptation in a cohort of Russian-speaking immigrants in Portugal (N = 555) did not account for mean satisfaction and availability responses, but did find a two-factor structure to be the best fit and tested high for reliability. 20 In the population of Russian-speaking immigrants, the two factors extracted using a factor analysis were number of supporters and satisfaction with social support received.…”
Section: Discussionmentioning
confidence: 97%
“… 20 , 21 An adaptation in a cohort of Russian-speaking immigrants in Portugal (N = 555) did not account for mean satisfaction and availability responses, but did find a two-factor structure to be the best fit and tested high for reliability. 20 In the population of Russian-speaking immigrants, the two factors extracted using a factor analysis were number of supporters and satisfaction with social support received. 20 Similarly, in a French population of university students (N = 348) and unemployed men (N = 304), the SSQ-6 yielded the two factors of availability and satisfaction.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Hudson et al [3,13] used the following measurement instruments for their studies: Carer Competence Scale [15], Preparedness for Caregiving Scale [16]; Family Inventory of Need [17], Rewards for Caregiver Scale [18], Social Support Questionnaire [19], Brief assessment scale for caregivers [15], Life Orientation Test [20]. Thus they were able to measure the caregivers' capability, their self-awareness about their own capability, their needs, the positive aspects of life, social support, the levels of weariness and optimism.…”
Section: Measurement Instrumentsmentioning
confidence: 99%